Homicide and violent crime - Deflem, Mathieu (Sociology of crime, law, and deviance ;, 2018)
This volume of "Sociology of Crime, Law and Deviance" addresses a variety of issues and concerns involved with the study of violent crime and homicide in the contemporary world. The chapters are conceived against the background of the enduring nature of violence and killing in the modern age, despite trends towards increased levels of civilization and the protection of rights. Whilst it is clear that the world of today is, in many respects, a better place, violence and homicide remain and even increase from time to time and from place to place. Each chapter tackles key questions of how and why these problematic forms of behaviour continue to exist. Specifically, chapters examine the killing of children, responses to domestic abuse, female killers, incidents of racial and religious violence, the dynamics of violence on college campuses, the role of police and state institutions in relation to violence, and global aspects of violence and murder. This book will be of interest to scholars and students in criminology, sociology, criminal justice, and public policy.